Assay interference and off-target liabilities of reported histone acetyltransferase inhibitors. Issue 1 (December 2017) - Dahlin, Jayme; Nelson, Kathryn; Strasser, Jessica; Barsyte-Lovejoy, Dalia; Szewczyk, Magdalena; Organ, Shawna; Cuellar, Matthew; Singh, Gurpreet; Shrimp, Jonathan; Nguyen, Nghi; Meier, Jordan; Arrowsmith, Cheryl; et al.
Abstract Many compounds with potentially reactive chemical motifs and poor physicochemical properties are published as selective modulators of biomolecules without sufficient validation and then propagated in the scientific literature as useful chemical probes. Several histone acetyltransferase (HAT) inhibitors with these liabilities are now routinely used to probe epigenetic pathways. We profile the most commonly used HAT inhibitors and confirm that the majority of them are nonselective interference compounds. Most (15 out of 23, 65%) of the inhibitors are flagged by ALARM NMR, an industry-developed counter-screen for promiscuous compounds. Biochemical counter-screens confirm that most of these compounds are either thiol-reactive or aggregators. Selectivity panels show many of these compounds modulate unrelated targets in vitro, while several also demonstrate nonspecific effects in cell assays. These data demonstrate the usefulness of performing counter-screens for bioassay promiscuity and assay interference, and raise caution about the utility of many widely used, but insufficiently validated, compounds employed in chemical biology. A substantial obstacle in basic research is the use of poorly validated tool compounds with purported useful biological functions. Here, the authors systematically profile widely used histone acetyltransferase inhibitors and find that the majority are nonselective interference compounds.